Model Penanaman Nilai Karakter Hindu Melalui Participatory Action Research (PAR) Pada Mahasiswa Pendidikan Agama Hindu STAHN Mpu Kuturan Singaraja - Subawa, Putu (Jurnal Penelitian Agama Hindu, 2025)
This research is motivated by the problem of character degradation of students of the Hindu Religious Education Study Program (PAH) STAHN Mpu Kuturan Singaraja, such as low social sensitivity, communication ethics that are not in line with manners, stagnation of academic-non-academic achievements, and minimal integration of Hindu values ​​in learning. These challenges threaten the competence of graduates as prospective educators and religious instructors in the era of digital disruption. The purpose of the research is to design a holistic Hindu character value instillation model through improvements in student input, lecturer methods, and the campus environment. The method used is qualitative Participatory Action Research (PAR) with three stages: (1) problem identification through observation, interviews, and document analysis; (2) intervention in the form of a Catur Guru workshop and integration of Tri Kaya Parisudha into the curriculum; (3) holistic evaluation combining cognitive, affective, and psychomotor aspects. The results of the study showed a significant increase in discipline (60% decrease in violations), dress code compliance (95%), student independence (80% of community organization activities without lecturer intervention), and integration of Hindu values ​​in learning. Supporting factors include the role of the family, a harmonious campus environment based on Tri Mandala, and collaboration with the community. In conclusion, the PAR-based character building model is effective in forming students with the characters of satyam, siwam, sundaram, although challenges such as consistency of administrative discipline still need to be overcome. This study contributes theoretically to the integration of Hindu values ​​(Sad Ripu, Dharma) into modern pedagogy and practically through recommendations for revitalizing the karma phala-based curriculum, strengthening the role of STAHN as a center of excellence for Hindu education in Indonesia.